The Problems of Word Formation in German - Mahmudova, Nigora (Jurnal Bahasa Daerah Indonesia, 2024)
The article examines the problem of word formation, models, types and styles of word formation, the opinions of a number of scientists dealing with the issues of word formation in German, and their classification based on the semantic principle.